Endovascular Treatment of Intracranial Aneurysms: Diversity in Treatment Techniques of Varying Anatomical Presentations - Patriawan Putu; Sitanggang Firman; Mohd Redzuan Ismail; Nik Azuan Nik Ismail; Nur Yazmin Yaacob; Ahmad Sobri Muda (Acta Medica Indonesiana)
We discuss and illustrate various endovascular treatment options for intracranial aneurysms, to reflect common technique used in endovascular treatment of brain aneurysm. We select five cases of various aneurysm types to show assortments of endovascular treatment (EVT) are performed. Selective catheterization of the intracranial aneurysms and endovascular treatments are technically feasible, offering a viable alternative to the surgical approach. We discuss the radiographic features, clinical presentation, and strategies of endovascular treatment of intracranial aneurysms.